A Lifespan Perspective on Embodied Cognition - Loeffler, Jonna; Raab, Markus; Cañal-Bruland, Rouwen (Frontiers in Psychology, 2016)
Since its infancy embodied cognition research has fundamentally changed our understanding of how action, perception, and cognition relate to and interact with each other. Ideas from different schools of thought have led to controversial theories and a unifying framework is still being debated. In this perspective paper we argue that in order to improve our understanding of embodied cognition and to take significant steps towards a comprehensive framework, a lifespan approach is mandatory. Given that most established theories have been developed and tested in the adult population, which is characterized by relatively robust and stable sensorimotor and cognitive abilities, we deem it questionable whether embodied cognition effects found in this population are representative for different life stages such as childhood or the elderly. In contrast to adulthood, childhood is accompanied by a rapid increase of sensorimotor and cognitive skills, and the old age by a decline of such capacities. Hence, sensorimotor and cognitive capacities, as well as their interactions, are more fragile at both extremes of the lifespan, thereby offering a unique window into the emergence of embodied cognition effects and age-related differences therein. A lifespan approach promises to make a major contribution towards a unifying and comprehensive theory of embodied cognition that is valid across the lifespan and ‘gets better with age’.